2018
DOI: 10.1590/0101-60830000000177
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in bipolar disorder: prevalence, demographics and clinical correlates in individuals with bipolar I, bipolar II, and healthy controls

Abstract: Background: The metabolic syndrome is a growing global public health problem and highly prevalent in patiens with bipolar disorder. There are a few studies about relationship between metabolic syndrome and bipolar disorder subtypes. Objective: The aim of this study was to investigate the prevalence of metabolic syndrome (MS) and its individual components in subjects with bipolar I (BD I) and bipolar II (BD II) disorder compared with non-psychiatric controls, and to determine the variables affecting MS. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…Our results showed that the most common physical comorbidity was obesity followed by CVD and liver dysfunctions. Similarly, previous studies have reported higher prevalence rates of obesity and suggested that treatment with psychotropic medications may worsen obesity . In turn, weight gain, excess weight, obesity, and metabolic disorders may increase the risk of cardiovascular disease in manic patients .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Our results showed that the most common physical comorbidity was obesity followed by CVD and liver dysfunctions. Similarly, previous studies have reported higher prevalence rates of obesity and suggested that treatment with psychotropic medications may worsen obesity . In turn, weight gain, excess weight, obesity, and metabolic disorders may increase the risk of cardiovascular disease in manic patients .…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, previous studies have reported higher prevalence rates of obesity and suggested that treatment with psychotropic medications may worsen obesity. [39][40][41] In turn, weight gain, excess weight, obesity, and metabolic disorders may increase the risk of cardiovascular disease Note: Numbers in bold indicate significant P (P < .05). Example: males significantly had a higher mean of readmission rate compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com a revisão conduzida por Grover et al (30), a frequência da síndrome metabólica em indivíduos portadores de TAB foi de 16.7%-67%, variando conforme os critérios diagnósticos utilizados e os países avaliados, que eram em sua maioria países ocidentais. Em outro estudo, a prevalência de síndrome metabólica em pacientes com TAB I foi maior que em pacientes com TAB II e controles saudáveis (31). Cada componente da síndrome costuma estar alterado na maioria dos estudos, sendo o aumento da circunferência abdominal a anormalidade mais consistentemente reportada (30,32).…”
Section: Discussionunclassified